IFNγ-Producing γ/δ T Cells Accumulate in the Fetal Brain Following Intrauterine Inflammation - Lewis, Emma L.; Tulina, Natalia; Anton, Lauren; Brown, Amy G.; Porrett, Paige M.; Elovitz, Michal A. (Frontiers in Immunology, 2021)
Intrauterine inflammation impacts prenatal neurodevelopment and is linked to adverse neurobehavioral outcomes ranging from cerebral palsy to autism spectrum disorder. However, the mechanism by which a prenatal exposure to intrauterine inflammation contributes to life-long neurobehavioral consequences is unknown. To address this gap in knowledge, this study investigates (1) how inflammation transverses across multiple anatomic compartments from the maternal reproductive tract to the fetal brain and (2) what specific cell types in the fetal brain may cause long-term neuronal injury. Utilizing a well-established mouse model, we found that mid-gestation intrauterine inflammation resulted in a lasting neutrophil influx to the decidua in the absence of maternal systemic inflammation. Fetal immunologic changes were observed at 72-hours post-intrauterine inflammation, including elevated neutrophils and macrophages in the fetal liver, and increased granulocytes and activated microglia in the fetal brain. Through unbiased clustering, a population of Gr-1+ T cells was identified as the earliest immune cell shift in the fetal brain of fetuses exposed to intrauterine inflammation and determined to be producing high levels of IFN when compared to T cells in other compartments. In a case-control study of term infants, IFN was found to be elevated in the cord blood of term infants exposed to intrauterine inflammation compared to those without this exposure. Collectively, these data identify a novel cellular immune mechanism for fetal brain injury in the setting of intrauterine inflammation.